(untitled) (Reflection and Critique Law Magazine, 2020)
The dignity of the human person is a peptide clause protected in the Constitution of the Federative Republic of Brazil of 1988, because it is a supreme law, orders and designates conducts for the set of infraconstitutional rules, disobedience is an offense before the Democratic Rule of Law. Nevertheless, the Labour Reform 2017 brought the figure of the intermittent employment contract, causing an affront to the positive legal system, as it breaks mainly with the principle of continuity of the employment relationship. Therefore, through the bibliographic methodology of articles and books, seeks to scrutinize their particularities and impacts on social rights that carry a framework of precariouslabour precariousness.